2020
DOI: 10.3390/designs4040046
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Firewood Consumption Patterns and CO2 Emission Patterns in Rural Households of Nepal

Abstract: Nepal has low per-capita energy use and a majority of its rural residents use firewood as their primary energy source. Excessive use of firewood in improperly ventilated buildings degrades the indoor environment and health condition of the inhabitants. This study aims to assess the influence of hourly firewood consumption patterns on CO2 emissions and resulting concentrations in rural households in Nepal. A field survey was conducted for 24 h in 16 households during winter. The results suggest that most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
4
6
1
Order By: Relevance
“…Annual amount per person (pns) of firewood used was 438 kg pens -1 year -1 and 141 kg pns -1 for charcoal in Koulikoro urban community. The same scenario of firewood consumption per person was observed in Nepal (Ram and Bahadur, 2020). However, spenditure in firewood was highest in large household group size and it was 2 times higher than in small household category size which recorded the lowest (Figure 10).…”
Section: Determination Of the Quantity Of The Most Consumed Energy So...supporting
confidence: 61%
“…Annual amount per person (pns) of firewood used was 438 kg pens -1 year -1 and 141 kg pns -1 for charcoal in Koulikoro urban community. The same scenario of firewood consumption per person was observed in Nepal (Ram and Bahadur, 2020). However, spenditure in firewood was highest in large household group size and it was 2 times higher than in small household category size which recorded the lowest (Figure 10).…”
Section: Determination Of the Quantity Of The Most Consumed Energy So...supporting
confidence: 61%
“…In terms of timing, as shown in Figure 3, the use of firewood for indoor space heating among the sample of survey respondents was consistent with previous research conducted in Australia [5], which found that firewood consumption was most common during the cooler months of the year, particularly May to September (peaking in July during the winter period). Research conducted in Nepal has also found that the consumption of firewood tends to be higher during the winter months [8]. In addition, as shown in Figures 3-5, the self-reported timing (i.e., months in the year), frequency (i.e., days per week), and duration (i.e., hours per day) of firewood consumption differed across geographical locations.…”
Section: What Socio-demographic Household and Dwelling-related Characteristics Are Significantly Associated With Firewood Consumption In mentioning
confidence: 86%
“…For example, developing more specific guidelines or instructions that help householders to accurately identify and report different wood species used for residential firewood, as well as more precise methods for converting between volume and weight for each species, could help to minimise the risk of measurement error, self-report biases, or other inaccuracies in retrospective reporting. Future studies could also consider implementing weight survey methodologies similar to those used in other international studies (for an example from Nepal, see [8,24]), where the weight of a firewood bundle is measured before and after firewood was burned. In addition, if the intention is to record and track firewood over an extended period (i.e., more longitudinal or repeated measures research), study participants could potentially use the weight survey method to keep a diary or written record of the amount of firewood consumed over a specific timeframe (e.g., during winter months).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations